2011
DOI: 10.5455/ijavms.20110215080443
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Different Agro-residues for Acid protease Production by Rhizopus sp. in Koji Fermentation

Abstract: Two different strains of Rhizopus sp. i.e. R. oligosporus-M30 and R. arrhizus-M26 were employed for the production of acid protease using different agro-residues such as rice husk, rice bran, wheat bran, defatted soybean meal and sunflower meal as a sole carbon source. R. oligosporus-M30 gave maximum enzyme level with soybean meal (15.6 U/gds) while R. arrhizus-M26 with sunflower meal (13.6 U/gds) respectively. The optimal conditions for the enzyme production by R .oligosporus-M30 were initial pH of 5.5, tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The optimum time in Figure 1 followed Rauf et al (2010), who found that the optimum time for enzyme synthesis from R. oligosporus occurred at 72 h for protease. Besides, Irfan et al (2011) showed similar optimum times in R. oligosporus for protease. In the other Rhizopus species, such as Rhizopus oryzae, the optimum time for enzyme synthesis occurred at an incubation period of 168 h (Mushtaq et al, 2015).…”
Section: Crude Enzyme Activitymentioning
confidence: 68%
“…The optimum time in Figure 1 followed Rauf et al (2010), who found that the optimum time for enzyme synthesis from R. oligosporus occurred at 72 h for protease. Besides, Irfan et al (2011) showed similar optimum times in R. oligosporus for protease. In the other Rhizopus species, such as Rhizopus oryzae, the optimum time for enzyme synthesis occurred at an incubation period of 168 h (Mushtaq et al, 2015).…”
Section: Crude Enzyme Activitymentioning
confidence: 68%
“…The inoculum of 30% promoted milk-clotting enzymes production by M. circinelloides cultivated in Indian grain bark (Sathya et al, 2009). The inoculums of 5% and 10% were considered as optimum for proteases production by R. arrhizus-M26 and R. oligosporus-M30, respectively (Irfan, Rauf, Syed, Nadeem, & Baig, 2011). A mutant species of Aspergillus flavus AS2 produced high quantitative of alkaline proteases using an inoculum size of 10% (Rani, Prasad, & Sambasivarao, 2012).…”
Section: Effect Of Different Parameters In the Milk-clotting Proteases Productionmentioning
confidence: 99%
“…In this research, the highest milk-clotting enzymes production by P. albidus was observed in the 10-day-age inoculum (74.0 U) (Figure 4). Rhizopus arrhizus M-26 produced enzymes at 8-day-age inoculum (Irfan et al, 2011) and A. flavus AS2 and R. oligosporus NCIM 1215 produced enzymes at 4-day-age inoculum (Prasad & Raju, 2013).…”
Section: Effect Of Different Parameters In the Milk-clotting Proteases Productionmentioning
confidence: 99%
“…Estudos revelaram que o tamanho do inóculo é um parâmetro que influencia na produção de proteases, independente da espécie avaliada e do bioprocesso. Por exemplo, a maior atividade proteolítica de Rhizopus oligosporus Saito 1905 M30 e de R. arrhizus A. Fisch 1892 M26 foi determinada quando utilizado inóculo de 10% e 5% (v/v), respectivamente (Irfan et al, 2011) Pleurotus albidus DPUA 1692 34,00 ± 0,00 a…”
Section: Influência Do Tamanho E Da Idade Do Inóculo Na Atividade Pro...unclassified